Mentorship-driven talent management : the Asian experience - Kumar, Payal; Budhwar, Pawan (Emerald Publishing Limited, 2020)
Evidence suggests that research on mentorship has been dominated by the West, and little is known about the cultural variations of the mentoring phenomenon. While some research has begun in emerging economies such as China and India, there is obviously a need for more research in different country contexts on the practice of mentoring, as well as its antecedents, intervening variables and expected outcomes in order to move the field forward. There is a need to identify the core theories and methodologies of mentorship which can be utilized to examine the Asian cultural context and the nuances of its management practices. This book aims to provide a deeper understanding of the contextual interpretation of mentoring by focusing on the Asian experience in countries such as China, India, Korea, Taiwan, Japan and Bangladesh. Shining a light on the importance of cross-cultural awareness and demographic dynamics when applied to talent management, it questions the positivist trend of decontextualizing HRM from the social-historical context of the workplace. It will provide business leaders and scholars with a critical understanding of what makes development, training and competency initiatives thrive in particular cultural contexts under the influence of larger historical and social structures. Heeding the call for mentoring relationships to be studied across cultures, this book on mentoring experiences in Asia is the need of the hour.
Includes index.
Print version record.
Keywords: Mentoring in business -- Asia; Personnel management -- Asia; Asians -- Career in business; Business & Economics, Mentoring & Coaching; Personnel & human resources management